Distribution and Ignorance - Juha Räikkä (Springer Netherlands, 2022)
According to the so-called presumption of equality, a person who does not know whether there is an acceptable reason for differential treatment should just presume the similarity of the cases and treat them equally. If we assume that the presumption of equality is an acceptable moral principle, at least when the allocation cannot be postponed and an equal distribution of goods is possible, then an important question arises: when exactly does the allocator have sufficient reasons for differential treatment and is not relevantly ignorant? This is a question about the required strength of the “acceptable reasons” for differential treatment. It has been commonplace to think that the presumption of equality demands that the reasons that refute the presumption must be very strong and that differential treatment requires that there is a proper justification for the claim that the cases are relevantly different. I will argue, however, that refuting the presumption and solving the issue (of whether the cases are relevantly similar or relevantly different) are two separate matters. A person can have good enough reasons for rejecting the presumption that the cases are relevantly similar without having reasons that she could present as a full justification for the claim that the cases are relevantly different. A precondition of the applicability of the presumption of equality is ignorance, but not ignorance in the sense of “not having a full justification”.